(untitled) (Archaeologia Adriatica, 2021)
The paper presents a study conducted by applying the method of archaeological field surveying. The survey was conducted on the Dinara mountain karst of the Jasenice and Obrovac areas. It defines the formation processes and the archaeological potential of the surveyed area. In addition, it discusses the applied methodology and its suitability for karst relief. It further presents the main characteristics of archaeological sources on karst terrain and categorises them by taking into account the material features and processes of Dinaric karst. The empirical data collected during the surveying are presented in chronological order.